(untitled) (Ameghiniana, 2020)
The cotylar fossa is a complex anatomical character in the astragalar medial malleolar facet. It represents a dynamic relationship between the astragalus and the tibia in the upper tarsal joint. The astragalus must accommodate the medial tibial malleolus when the tibia is in an extreme flexion. It is one of the three morphological synapomorphies considered for Afrotheria, although it is also a recurrent trait among different groups of mammals. Here, fossil South American Native Ungulates and extant mammals were surveyed to reevaluate how much this character is spread and how variable it is. Beyond afrotherians, it is observed that it also appears in primates, macropodid marsupials, laurasiatherian archaic ungulates, perissodactyls, pantodonts, and dinoceratans; it is also in some but not all of the extinct endemic ungulates from South America. No function has been suggested before for the presence of a cotylar fossa. The cotylar fossa could be an adaptation to a passive, rest related posture. Extreme flexion of the tibia/fibula over the foot happens when animal sits or lies down. Because of this, the cotylar fossa may not represent a synapomorphy of afrotherians but a homoplastic feature convergently developed several times. The cotylar fossa, as first described, is more characteristic of the order Primates than of any other taxa, including Afrotheria. But, there is more than one kind of cotylar fossa, and this variation could correspond to more than one cause, including phylogenetic constraints.